1989
DOI: 10.1007/bf02327266
|View full text |Cite
|
Sign up to set email alerts
|

A new method for determining the relation between soil- and plant-cadmium

Abstract: On soils differing in total Cd concentration, organic matter content and pH, but with the same compost treatment, a significant linear relation was found between the calculated Cd 2+ concentration of the soil solution and the Cd concentration of lettuce grown under field conditions. The Cd 2+ concentration was calculated with the equation for the exchange reaction between Cd 2 § and Ca 2+ .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…In contrast to available Cd determined by extractions, exchangeable Cd is the fraction of total Cd that is potentially available for plant uptake [67]. This implicates CEC as a relevant, albeit minor soil variable, which is borne out here (Fig 5A, S6 Table in S1 File) and supported more generally by the control of CEC on Cd 2+ in soil solution [68,69]. Sequential extraction methods are often used to separate the total Cd pool into standardized fractions defined by chemical solubility [4], which in some cases approximate conceptual pools such as bioavailable or parent material Cd [70,71].…”
Section: Plos Onesupporting
confidence: 53%
“…In contrast to available Cd determined by extractions, exchangeable Cd is the fraction of total Cd that is potentially available for plant uptake [67]. This implicates CEC as a relevant, albeit minor soil variable, which is borne out here (Fig 5A, S6 Table in S1 File) and supported more generally by the control of CEC on Cd 2+ in soil solution [68,69]. Sequential extraction methods are often used to separate the total Cd pool into standardized fractions defined by chemical solubility [4], which in some cases approximate conceptual pools such as bioavailable or parent material Cd [70,71].…”
Section: Plos Onesupporting
confidence: 53%
“…In contrast to available Cd determined by extractions, exchangeable Cd is the fraction of total Cd that is potentially available for plant uptake [67]. This implicates CEC as a relevant, albeit minor soil variable, which is borne out here (Fig 5A, S6 Table in S1 File) and supported more generally by the control of CEC on Cd 2+ in soil solution [68,69]. Sequential extraction methods are often used to separate the total Cd pool into standardized fractions defined by chemical solubility [4], which in some cases approximate conceptual pools such as bioavailable or parent material Cd [70,71].…”
Section: Plos Onesupporting
confidence: 53%
“…Similarly, Gerzabek et al (1998) found an increase in mobile fractions of Cd after sewage sludge application, but heavy metal uptake by plants did not respond proportionately. Also, Van Erp and Van Lune (1989) found a low Cd availability in soil treated with metal‐contaminated compost compared with untreated soil, even though they considered Cd speciation in their assessment.…”
Section: Discussionmentioning
confidence: 99%